Stability of long-run money demand function : evidence from Malaysia - Abdul Manap, Turkhan Ali (KENMS-IIUM Press, 2009)

(untitled)
There has been extensive theoretical and empirical research on the subject of money demand. The usefulness of a money demand function in the conduct of monetary policy depends critically on its stability. This paper studies the stability of the M1 and M2 money demand functions for Malaysia. The results show that both M1 and M2 are cointegrated with their determinants. However, only the long-run parameter of M1 demand function is stable over the sample period but not M2. The demand function for M2 becomes unstable after 1997, which coincides with the Asian financial crisis. This result contradicts that of Nair et al. (2008) who claim that the Asian financial crisis does not have any influence on the stability of money demand function in Malaysia. Our findings also mean that a simple relationship between M2, income and interest rate characterized by the standard model is not sufficient for analyzing the effects of Malaysian monetary policy.